Tapping into market opportunities in aging societies - the example of advanced driver assistance systems in the transition to autonomous driving. (22nd February 2021) - Günthner, Timo; Proff, Heike; Jovic, Josip; Zeymer, Lukas
The stagnation in car sales in the triad markets is forcing automotive companies to seek new market opportunities, e.g., in the aging society. The number of older drivers is growing, and they can afford safety- and comfort-related products which allow them to drive into older age despite physical and psychological restrictions. Therefore, potentials for advanced driver assistance systems for elderly drivers are likely to exist in these markets. By determining older drivers' willingness to pay for advanced driver assistance systems in the transition to autonomous driving, market opportunities can be identified. This study proves that there are market potentials for these systems in the 'silver market'. However, there is no simple linear relationship between age and willingness to pay. A more thorough examination is therefore needed.